FAKTOR â€“ FAKTOR YANG MEMPENGARUHI NIAT BERWIRAUSAHA MAHASISWA - Walipah, Walipah; Naim, Naim (Jurnal Ekonomi Modernisasi, 2016)
Socio-economic issues such as poverty, unemployment productive age are a major challenge for Indonesia when entering the free market and global competition. As one of the leading Human Resources, college needs to know the factors that influence students in entrepreneurship. Various factors that influence entrepreneurial intentions in students, especially the attitude and contextual factors. Population isÂ  Economic Education Student in Universtas Kanjuruhan Malang. Data were analyzed using multiple linear regression. The results of this study indicate that the attitude positive effect on entrepreneurial intention of students, while the contextual factors positively affects student entrepreneurial intention.